STUDY OF HEMOGLOBIN IN VEGETARIAN AND NON-VEGETARIAN DIET IN OBESE WOMEN WITH RISK OF CARDIAC PROBLEM IN LUCKNOW CITY - Shyam Vinay Sharma; Sciddhartha Koonwar; Virendra Atam; Uma Singh; M L Patel (National Journal of Medical Research, 2013)
Introduction: Hemoglobin level and pattern of food intake is closely associated with risk of cardiovascular diseases. The cardiovascular diseases are primarily may be due to altered lipid profile which is depend on type and pattern of food intake. Association of vegetarian and non-vegetarianisms in obese women is controversial.